2007
DOI: 10.1088/0951-7715/20/2/002
|View full text |Cite
|
Sign up to set email alerts
|

Homoclinic tangencies of arbitrarily high orders in conservative and dissipative two-dimensional maps

Abstract: We show that maps with homoclinic tangencies of arbitrarily high orders and, as a consequence, with arbitrarily degenerate periodic orbits are dense in the Newhouse regions in spaces of real-analytic area-preserving two-dimensional maps and general real-analytic two-dimensional maps (the result was earlier known only for the space of smooth non-conservative maps). Based on this, we show that a generic area-preserving map from the Newhouse region is 'universal' in the sense that its iterations approximate the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(106 citation statements)
references
References 50 publications
(104 reference statements)
5
99
0
2
Order By: Relevance
“…(c) Similar results related to finite-smooth normal forms of saddle maps were established in [8,14,17,20] for general, near-conservative and conservative maps. In this paper we, in fact, modify the corresponding proofs adapting them to the reversible case.…”
Section: Preliminary Geometric and Analytic Constructionssupporting
confidence: 75%
See 3 more Smart Citations
“…(c) Similar results related to finite-smooth normal forms of saddle maps were established in [8,14,17,20] for general, near-conservative and conservative maps. In this paper we, in fact, modify the corresponding proofs adapting them to the reversible case.…”
Section: Preliminary Geometric and Analytic Constructionssupporting
confidence: 75%
“…Precisely, it will be shown that in some regions of the space of parameters (c,M ) the map T km possesses chaotic dynamics and has four saddle fixed points, two of them symmetric conservative and a symmetric couple of fixed points (that is, symmetric one to each other and with Jacobian greater and less than 1, respectively). According to [12,23,20], the following result holds:…”
Section: A Short Description Of the Main Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then for any sufficiently C 3 -close approximation of H (1) by an analytic Hamiltonian [the analiticity of H (1) and H (2) is needed for the family Φ μ to be analytic, i.e. lie in V N ] conditions (75) and (78) will still be satisfied (the idea of constructing analytic perturbations by approximating smooth parametric families of perturbations can be traced back to [16], it was also used in [51]). …”
Section: Lemma 5 For Every Family Of Mapsmentioning
confidence: 99%